Work related values and attitudes in Central and Eastern Europe - Agnes Borgulya; Judit Hahn (Journal for East European Management Studies, 2008)
After the shift from centrally planned to market economies, CEE countries experienced significant changes in the world of work. Full employment was replaced by a distortion in labour markets, a rapid rise in unemployment and intensive labour emigration. The following questions are discussed: (1) Can the people in CEE countries be characterized by similar work-related values? (2) Is there any diversity in attitudes towards superiors in the transition countries? To answer these questions, findings of the European Values Study are used. The comparison of data from fourteen CEE countries shows that, concerning workrelated values, two groups of countries can be differentiated. The analysis of attitudes towards one's superior also suggests the lack of a homogenous Eastern European cluster. – – Nach dem Beginn des Übergangs von der Zentralverwaltungs- zur Marktwirtschaft hat sich die Arbeitswelt in den MOE-Ländern dramatisch verändert. Die frühere Vollbeschäftigung wurde durch den Zusammenbruch des Arbeitsmarktes abgelöst, was zu hohen Arbeitslosenraten und nachher zu einer Arbeitsmigration geführt hat. In diesem Beitrag wir die Antwort auf folgende Frage gesucht: Haben die Arbeitnehmer in den untersuchten vierzehn MOELändern nach den Wertänderungen gleiche arbeitsbezogene Werte und gleiche Attitüden zu ihren Vorgesetzten? Um diese Fragen beantworten zu können, stützen sich die Verfasser auf die Datei der internationalen Erhebung European Values Study. Auf Grund der arbeitsbezogenen Werte konnten zwei Gruppen unterschieden werden. Die Analyse der Attitüde zum Vorgesetzten hat zum Vorschein gebracht, dass die untersuchten MOE-Länder in dieser Hinsicht nicht homogen sind.
Keywords: 650; Work-related values; attitudes; Central and Eastern Europe; European Values Study